2018
DOI: 10.7181/acfs.2018.02124
|View full text |Cite
|
Sign up to set email alerts
|

A giant trichoblastic carcinoma

Abstract: Trichoblastic carcinoma usually occurs as a malignant transformation of the trichoblastoma, but is very rare. A 25-year-old man was admitted with trichoblastoma in the nuchal area with frequent recurrences since birth. The preoperative neck magnetic resonance image revealed lobulated soft tissue lesions involving superficial fascia and infiltrating into both proximal trapezius muscles. In our department, wide excision and reconstruction with a free anterolateral thigh flap were performed. Histological examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Malignant trichoblastoma has only been described in case reports in the literature. Pigmented forms such as trichoblastomas and giant forms have also been reported [14,15]. As in our patients, these lesions mostly affect the head and neck region [16] and the elderly, although, other locations such as the abdomen [17] and the paraspinal area [18] may also be involved.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Malignant trichoblastoma has only been described in case reports in the literature. Pigmented forms such as trichoblastomas and giant forms have also been reported [14,15]. As in our patients, these lesions mostly affect the head and neck region [16] and the elderly, although, other locations such as the abdomen [17] and the paraspinal area [18] may also be involved.…”
Section: Discussionsupporting
confidence: 69%
“…The primary form of treatment reported in the literature involves surgical excision. There is no clear-cut consensus regarding the surgical margins, with some studies reporting excisions ranging between 0.5 cm and 1.5 cm [13][14][15]. In our patient, excision was performed to achieve a surgical margin of 1 cm, with primary repair.…”
Section: Discussionmentioning
confidence: 85%
“…Trichoblastic carcinoma (TBC), or malignant trichoblastoma, is a rare malignant adnexal neoplasm. TBC is conventionally thought to develop within pre-existing trichoblastoma [ 1 ] but can also occur within trichoepithelioma in conjunction with genodermatoses such as multiple familial trichoepitheliomas or Brooke-Spiegler syndrome [ 2 - 4 ]. In contrast to prior views, a recent retrospective review reported that most cases (87%) seemed to have occurred spontaneously, though the authors noted that pre-existing benign lesions might have gone undetected before the diagnosis of TBC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%